Rapid diagnostic tests for typhoid and paratyphoid (enteric) fever - Wijedoru, Lalith (Cochrane Database Syst Rev, 2017)
BACKGROUND: Differentiating both typhoid (Salmonella Typhi) and paratyphoid (Salmonella Paratyphi A) infection from other causes of fever in endemic areas is a diagnostic challenge. Although commercial point‐of‐care rapid diagnostic tests (RDTs) for enteric fever are available as alternatives to the current reference standard test of blood or bone marrow culture, or to the widely used Widal Test, their diagnostic accuracy is unclear. If accurate, they could potentially replace blood culture as the World Health Organization (WHO)‐recommended main diagnostic test for enteric fever. OBJECTIVES: To assess the diagnostic accuracy of commercially available rapid diagnostic tests (RDTs) and prototypes for detecting Salmonella Typhi or Paratyphi A infection in symptomatic persons living in endemic areas. SEARCH METHODS: We searched the Cochrane Infectious Diseases Group Specialized Register, MEDLINE, Embase, Science Citation Index, IndMED, African Index Medicus, LILACS, ClinicalTrials.gov, and the World Health Organization (WHO) International Clinical Trials Registry Platform (ICTRP) up to 4 March 2016. We manually searched WHO reports, and papers from international conferences on Salmonella infections. We also contacted test manufacturers to identify studies. SELECTION CRITERIA: We included diagnostic accuracy studies of enteric fever RDTs in patients with fever or with symptoms suggestive of enteric fever living in endemic areas. We classified the reference standard used as either Grade 1 (result from a blood culture and a bone marrow culture) or Grade 2 (result from blood culture and blood polymerase chain reaction, or from blood culture alone). DATA COLLECTION AND ANALYSIS: Two review authors independently extracted the test result data. We used a modified QUADAS‐2 extraction form to assess methodological quality. We performed a meta‐analysis when there were sufficient studies for the test and heterogeneity was reasonable. MAIN RESULTS: Thirty‐seven studies met the inclusion criteria and included a total of 5080 participants (range 50 to 1732). Enteric fever prevalence rates in the study populations ranged from 1% to 75% (median prevalence 24%, interquartile range (IQR) 11% to 46%). The included studies evaluated 16 different RDTs, and 16 studies compared two or more different RDTs. Only three studies used the Grade 1 reference standard, and only 11 studies recruited unselected febrile patients. Most included studies were from Asia, with five studies from sub‐Saharan Africa. All of the RDTs were designed to detect S.Typhi infection only. Most studies evaluated three RDTs and their variants: TUBEX in 14 studies; Typhidot (Typhidot, Typhidot‐M, and TyphiRapid‐Tr02) in 22 studies; and the Test‐It Typhoid immunochromatographic lateral flow assay, and its earlier prototypes (dipstick, latex agglutination) developed by the Royal Tropical Institute, Amsterdam (KIT) in nine studies. Meta‐analyses showed an average sensitivity of 78% (95% confidence interval (CI) 71% to 85%) and specificity of 87% (95% CI 82% to 91%) for TUBEX; and an average sensitivity of 69% (95% CI 59% to 78%) and specificity of 90% (95% CI 78% to 93%) for all Test‐It Typhoid and prototype tests (KIT). Across all forms of the Typhidot test, the average sensitivity was 84% (95% CI 73% to 91%) and specificity was 79% (95% CI 70% to 87%). When we based the analysis on the 13 studies of the Typhidot test that either reported indeterminate test results or where the test format means there are no indeterminate results, the average sensitivity was 78% (95% CI 65% to 87%) and specificity was 77% (95% CI 66% to 86%). We did not identify any difference in either sensitivity or specificity between TUBEX, Typhidot, and Test‐it Typhoid tests when based on comparison to the 13 Typhidot studies where indeterminate results are either reported or not applicable. If TUBEX and Test‐it Typhoid are compared to all Typhidot studies, the sensitivity of Typhidot was higher than Test‐it Typhoid (15% (95% CI 2% to 28%), but other comparisons did not show a difference at the 95% level of CIs. In a hypothetical cohort of 1000 patients presenting with fever where 30% (300 patients) have enteric fever, on average Typhidot tests reporting indeterminate results or where tests do not produce indeterminate results will miss the diagnosis in 66 patients with enteric fever, TUBEX will miss 66, and Test‐It Typhoid and prototype (KIT) tests will miss 93. In the 700 people without enteric fever, the number of people incorrectly diagnosed with enteric fever would be 161 with Typhidot tests, 91 with TUBEX, and 70 with Test‐It Typhoid and prototype (KIT) tests. The CIs around these estimates were wide, with no difference in false positive results shown between tests. The quality of the data for each study was evaluated using a standardized checklist called QUADAS‐2. Overall, the certainty of the evidence in the studies that evaluated enteric fever RDTs was low. AUTHORS' CONCLUSIONS: In 37 studies that evaluated the diagnostic accuracy of RDTs for enteric fever, few studies were at a low risk of bias. The three main RDT tests and variants had moderate diagnostic accuracy. There was no evidence of a difference between the average sensitivity and specificity of the three main RDT tests. More robust evaluations of alternative RDTs for enteric fever are needed. 2 April 2019 Up to date All studies incorporated from most recent search All eligible published studies found in the last search (4 Mar, 2016) were included